The Use Of Aquafaba, Plant Protein Isolate And Soy Lecithin To Replace Egg In Kuih Bahulu - Rahman, Rosmiza Abd (Universiti Sains Malaysia, 2020)
Egg is a one of the main ingredients in producing kuih bahulu due to the excellent functional properties, but there are popping up some problem prone to the allergies and vegan. Thus, give an impact to the food industry especially local food industry to find the suitable substitution for the egg. In this study, different ingredients (aquafaba, plant protein isolate and soy lecithin) were used with different combination in sample such as AQ, PPI, AQ and PPI, and lastly PAS to replace egg in producing kuih bahulu to study the effect on physical quality of kuih bahulu. Test on the appearance, specific volume, crust and crumb colour and texture including hardness, chewiness and springiness were performed on all samples. Appearance in terms of size and colour were observed and showed that the sample with SL was almost like the control sample. Most of the analysis result showed that there were significant different (P < 0.05) between control sample and PAS sample in terms of specific volume, L* and ho for the crust colour, ho for the crumb colour and hardness of sample texture. However, the PAS was almost similar to the control sample and sample with PAS was much better compared to control sample in terms of texture. However, it is possible to make eggfree kuih bahulu due to the excellent functional properties of egg, and the further research on the combination of plant-based ingredients to replace egg is required.